Solid oxide fuel cell and method for producing solid oxide fuel cell
By employing aluminum-containing ferritic stainless steel for interconnectors in solid oxide fuel cells and using insert members with low mutual diffusion coefficients, the corrosion issues faced by thinner interconnectors are addressed, ensuring effective suppression of corrosion and maintaining the structural integrity and performance of the fuel cell.
Patent Information
- Application Number
- JP2023527210
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-08
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-06-08
AI Technical Summary
Existing solid oxide fuel cells with interconnectors made of ferritic stainless steel face corrosion issues, particularly when thinner interconnectors are required for higher output density applications, such as in-vehicle use.
The use of aluminum-containing ferritic stainless steel (AL-containing FSS) for the interconnectors, which forms a thin alumina layer on the surface during operation, thereby suppressing corrosion. Additionally, insert members with a lower mutual diffusion coefficient with aluminum, such as nickel, are used to stabilize the alumina layer formation.
This configuration effectively suppresses corrosion of the interconnectors even at thinner thicknesses, ensuring the structural integrity and performance of the fuel cell, particularly in high-output density applications.
Smart Images

Figure 0007655383000001 
Figure 0007655383000002 
Figure 0007655383000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid oxide fuel cell and a method for producing a solid oxide fuel cell. [Background technology]
[0002] JP2006-236989A discloses a fuel cell in which a plurality of unit cells, each having a metal supporting substrate on both sides of a membrane electrode assembly, are stacked via an interconnector made of ferritic stainless steel as a base material. Summary of the Invention
[0003] Although the interconnector based on ferritic stainless steel has a problem of corrosion during use of the fuel cell, the above-mentioned document does not disclose any measures to suppress the corrosion. The above-mentioned document describes the thickness of the interconnector as 0.5-1.5 mm. This is considered to be because the sufficient thickness prevents the interconnector from deteriorating, such as by forming holes, even if corrosion progresses.
[0004] However, when a higher power density is required, such as for on-board use, the thickness of the interconnector needs to be thinner, and therefore it is not possible to prevent deterioration due to corrosion of the interconnector by providing a sufficient thickness, as in the above-mentioned document.
[0005] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide a fuel cell capable of suppressing corrosion of the interconnector.
[0006] According to one aspect of the present invention, there is provided a solid oxide fuel cell in which a plurality of power generating cells, each having a solid electrolyte plate, an anode electrode disposed on one surface of the solid electrolyte plate, an anode support layer supporting the anode electrode, a cathode electrode disposed on the other surface of the solid electrolyte plate, and a cathode support layer supporting the cathode electrode, are stacked in the thickness direction via an interconnector that electrically connects the anode support layer of one adjacent power generating cell to the cathode support layer of the other adjacent power generating cell. The anode support layer and the cathode support layer are made of ferritic stainless steel, and the interconnector is made of aluminum. At a content of 2wt% or more It is made of ferritic stainless steel containing [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view of a solid oxide fuel cell according to an embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged view of region II in FIG. [Diagram 3] FIG. 3 is an enlarged view of region III in FIG. [Figure 4] FIG. 4 is a schematic cross-sectional view of a solid oxide fuel cell according to a modified example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.
[0009] FIG. 1 is a schematic cross-sectional view of a stack of a power generation unit 1 constituting a power generation module of a solid oxide fuel cell (hereinafter also simply referred to as a "fuel cell") according to this embodiment.
[0010] The power generation unit 1 comprises a power generation cell 2, a cell frame 3 that supports the outer edge of the power generation cell 2, and an interconnector 4 that is joined to the anode support layer 2D and the cell frame 3.
[0011] The power generating cell 2 is composed of a membrane electrode assembly 2C in which an anode electrode is formed on one surface of a solid electrolyte plate and a cathode electrode is formed on the other surface, a cathode support layer 2B that supports the cathode electrode, and an anode support layer 2D that supports the anode electrode. Both the cathode support layer 2B and the anode support layer 2D are formed of a metal, for example, ferritic stainless steel (hereinafter also referred to as FSS).
[0012] The interconnector 4 is formed from a single plate material whose base material is ferritic stainless steel containing aluminum (hereinafter also referred to as AL-containing FSS). In the stacked state, a cathode side rib 10 protruding toward the cathode electrode of one power generation unit 1 and an anode side rib 11 protruding toward the anode electrode of the other power generation unit 1 are provided by pressing or the like.
[0013] The joining of the anode-side rib 11 and the anode support layer 2D (joint 7 in the figure) and the joining of the interconnector 4 and the cell frame 3 (joint 6 in the figure) can be performed by a method such as welding or joining using an insert member, but in this embodiment, joining using an insert member is used. The insert member to be used will be described later.
[0014] The two power generating units 1 are stacked by metal-joining the cathode rib 10 of one power generating unit 1 to the power generating cell 2 of the other power generating unit 1 by a method other than welding, for example, by joining using an insert member (joint 5 in the figure). In other words, the interconnector 4 has the function of electrically connecting the anode electrode and cathode electrode adjacent to it. When stacking even more power generating units 1, the power generating units 1 are similarly metal-joined to each other by diffusion bonding or the like. Welding is not used as a method of joining the power generating units 1 to each other because a welder cannot access the contact part between the cathode rib 10 and the power generating cell 2 when the power generating units 1 are in contact with each other.
[0015] The joining of the joints 5 and 6 using the insert members will be described later.
[0016] The configuration of the power generation unit 1 is not limited to the above. For example, a power generation unit 1 may be formed by welding an interconnector 4 to the cathode support layer 2B of a power generation cell 2, and the interconnector 4 of this power generation unit 1 may be metal-bonded to the anode support layer 2D of another power generation unit 1.
[0017] By joining the cathode side rib 10 and the cathode support layer 2B, a space surrounded by one surface of the interconnector 4 and the cathode support layer 2B is formed. This space is defined as a cathode flow path 8 through which the cathode gas flows. On the other hand, by joining the anode side rib 11 and the anode support layer 2D, a space surrounded by the other surface of the interconnector 4 and the anode support layer 2D is formed. This space is defined as an anode flow path 9 through which the anode gas flows. In other words, the interconnector 4 also functions as a partition plate that separates the cathode flow path 8 and the anode flow path 9. Note that, when the flow rate of the cathode gas flowing through the cathode flow path 8 is compared with the flow rate of the anode gas flowing through the anode flow path 9, the flow rate of the cathode gas is greater.
[0018] With the above configuration, a current flows from the anode electrode of the power generating unit 1 at the lower part of the figure through the interconnector 4 to the cathode electrode of the power generating unit 1 at the upper part of the figure.
[0019] During operation of the fuel cell, the anode electrode generating reaction heat becomes a heat generating part, and the temperature of the anode side including the anode support layer 2D rises. In the fuel cell of this embodiment, the anode support layer 2D supporting the anode electrode is configured to contact not only the anode flow path 9 but also the cathode flow path 8 via the anode side rib 11. That is, the anode support layer 2D is in contact with the cathode flow path 8 through which the cathode gas flows at a flow rate greater than that of the anode gas, and thus heat exchange between the anode support layer 2D and the cathode gas is promoted, and as a result, cooling of the anode side is promoted. Furthermore, by cooling the anode side, steam oxidation, which will be described later, is suppressed, and therefore corrosion of the interconnector 4 can be suppressed.
[0020] When the interconnector 4 is made of FSS, there is a problem as to how to prevent the interconnector 4 from corroding.
[0021] The fuel cell becomes hot during operation, and the surface of the interconnector 4 that forms the cathode flow path 8 (also referred to as the cathode side surface) is exposed to air. As a result, the cathode side surface of the interconnector 4 is prone to oxidation due to oxygen in the air (hereinafter, this oxidation is also referred to as atmospheric oxidation). On the other hand, the surface of the interconnector 4 that forms the anode flow path (also referred to as the anode side surface) is exposed to water vapor generated by the reaction, and is prone to oxidation due to water vapor (hereinafter, this oxidation is also referred to as water vapor oxidation). These oxidations cause the interconnector 4 to corrode.
[0022] Hydrogen also has the property of diffusing inside the interconnector 4 made of FSS. When the diffused hydrogen moves from the anode side interface to the cathode side interface inside the interconnector 4, it combines with the air flowing through the cathode flow channel 8 to generate water, which causes corrosion (this is called dual corrosion). Dual corrosion is particularly likely to occur in the case of an interconnector 4 that is formed thinly by press molding or the like.
[0023] In addition, corrosion can also occur due to the chromium contained in the FSS for corrosion resistance evaporating under high temperature conditions (hereinafter, this type of corrosion is also referred to as Cr evaporative corrosion).
[0024] As the above-mentioned atmospheric oxidation, steam oxidation, dual corrosion, and Cr evaporation (hereinafter collectively referred to as "corrosion") progress, the interconnector 4 deteriorates (specifically, strength reduction, hole formation, etc.). As a measure to prevent deterioration due to atmospheric oxidation, steam oxidation, and dual corrosion, it is possible to increase the thickness of the substrate of the interconnector 4. In other words, deterioration can be prevented by making the thickness such that strength can be ensured even if corrosion progresses and holes will not be formed. However, when the above-mentioned fuel cell is mounted on a vehicle, that is, when it is used as a driving source for the vehicle, and a higher output density is required, it is desirable for the plate thickness of the interconnector 4 to be thin in order to suppress the dimension in the thickness direction, and therefore this measure is not appropriate.
[0025] In addition, while atmospheric oxidation can be suppressed by lowering the operating temperature range of the fuel cell, the temperature range in which steam oxidation can be suppressed is very narrow, and this temperature range is different from the operating temperature range of the fuel cell (for example, 600-750°C). In addition, Cr evaporation and dual corrosion cannot be addressed by adjusting the operating temperature range of the fuel cell.
[0026] Therefore, in this embodiment, as described above, an Al-containing FSS is used as the substrate of the interconnector 4. This is to suppress corrosion by forming a thin alumina layer on the outermost surface of the interconnector 4 during the operation of the fuel cell or during the stacking process, and to ensure corrosion resistance even if the plate thickness of the interconnector 4 is thin. This will be described with reference to Figs. 2 and 3. Fig. 2 is an enlarged view of region II in Fig. 1. Fig. 3 is an enlarged view of region III in Fig. 2.
[0027] First, the mechanism by which the alumina layer is formed will be described. First, aluminum near the surface of the interconnector 4 is oxidized to form an alumina layer 12 on the outermost surface of the interconnector 4. This creates an aluminum concentration gradient in the interconnector 4, with the aluminum being thin near the surface (hereinafter also referred to as the surface side) and thick near the center (hereinafter also referred to as the center side). This concentration gradient acts as a driving force to move the aluminum from the center side to the surface side (in the direction of the arrow in Figure 3), further forming the alumina layer.
[0028] In this embodiment, the aluminum content of the Al-containing FSS used as the substrate of the interconnector 4 is desirably 2 wt % or more. This is because an alumina layer is stably formed as the outermost surface layer of the substrate, thereby making it possible to suppress corrosion of the interconnector 4.
[0029] Also, it is desirable that the aluminum content of the AL-containing FSS is 10 wt% or less. The reason is as follows. When the aluminum content of the AL-containing FSS exceeds 10 wt%, the bonding state changes from a solid solution with metallic bonds to an intermetallic compound with ionic or covalent bonds. As is generally known, ionic and covalent bonds are harder but have lower toughness than metallic bonds. In other words, when the aluminum content exceeds 10 wt%, the toughness decreases and there is a risk that the strength against the compressive load applied in the lamination process and vibrations while mounted on a vehicle cannot be maintained.
[0030] The thickness W1 of the AL-containing FSS described above is thinner than the thickness W2 of the cathode support layer 2B. The same holds true for the anode support layer 2D, where the thickness W1 of the AL-containing FSS is thinner than the thickness of the anode support layer 2D. If the interconnector 4 is thicker than the support layers 2B, 2D, even if the support layers 2B, 2D are made of metal, the strength may be insufficient to withstand the compressive load input from the interconnector 4 to the power generation cell 2 in the lamination process. Therefore, by making the interconnector 4 thinner than the support layers 2B, 2D, the balance between the compressive load and the strength of the support layers 2B, 2D is optimized.
[0031] Next, the insert member 13 used in the joints 5 and 6 will be described.
[0032] At the joints 5 and 6, if the aluminum contained in the interconnector 4 flows out into the support layers 2B and 2D and the aluminum content of the interconnector 4 falls below 2 wt%, it becomes difficult to form the alumina layer 12 on the outermost layer of the interconnector 4. In particular, if the interconnector 4 and the support layers 2B and 2D are directly joined by welding, diffusion bonding or the like without using the insert member 13, the FSS and the Al-containing FSS come into contact with each other at the joints 5 and 6, making it easier for the aluminum to flow out. Therefore, the insert member 13 is used, which is mainly composed of a material that has a smaller mutual diffusion coefficient with aluminum than in the case of direct bonding.
[0033] Nickel, for example, can be given as a main component of the insert member 13. The mutual diffusion coefficient between nickel and aluminum is extremely small, about 1 / 10,000 to 1 / 100,000 of the mutual diffusion coefficient between FSS and aluminum, so that outflow of aluminum from the interconnector 4 to the insert member 13 is suppressed, and the alumina layer 12 can be stably formed.
[0034] Instead of using a material having a small mutual diffusion coefficient with aluminum as described above, a material containing aluminum (for example, an AL-containing FSS) may be used as the insert member 13. If the insert member 13 contains aluminum, the aluminum concentration gradient between the interconnector 4 and the insert member 13 becomes small, and outflow of aluminum from the interconnector 4 to the insert member 13 is suppressed. Note that a material containing aluminum and mainly composed of nickel may be used as the insert member 13.
[0035] Furthermore, when using an Al-containing FSS as the insert member 13, a paste is more preferable than a foil material because the aluminum content can be adjusted more easily with a paste, and the heating temperature in the joining process can be reduced.
[0036] In the above configuration, the formation of an alumina layer begins on the outermost surface of the interconnector 4 during the stacking process in which multiple power generation units 1 are stacked or during operation of the fuel cell. In other words, an alumina layer is not formed on the outermost surface of the interconnector 4 prior to the stacking process. However, a pre-oxidation process may be performed in which the interconnector is oxidized before the stacking process. "Before the stacking process" here may mean immediately before the stacking process, before forming the interconnector 4, or after forming it.
[0037] By carrying out the pre-oxidation step, the period during which the alumina layer is formed during the operation of the fuel cell can be shortened, thereby improving the steam oxidation resistance at lower temperatures, such as during start-up.
[0038] In the pre-oxidation step, the interconnector 4 is heated to 900°C or higher. By performing the oxidation treatment at 900°C or higher, the alumina layer formed becomes so-called alpha alumina. Since alpha alumina has the characteristics of being highly stable and not prone to abnormal growth, the supply rate of aluminum for forming the alumina layer can be suppressed. As a result, it becomes possible to maintain steam oxidation resistance for a long period of time.
[0039] Next, a modification of this embodiment will be described, which also falls within the scope of the present invention, just like this embodiment.
[0040] FIG. 4 is a schematic cross-sectional view of a stack of power generation units 1 constituting a power generation module of a fuel cell according to this modified example.
[0041] In FIG. 1, the width of the contact portion between the anode side rib 11 and the anode support layer 2D (i.e., joint 7) is equal to the width of the contact portion between the cathode side rib 10 and the cathode support layer 2B (i.e., joint 5). In contrast to this, in this modification, as shown in FIG. 4, the width of the joint 7 is wider than the width of the joint 5. In other words, the configuration of this modification has a larger contact area between the anode support layer 2D and the cathode flow path 8, i.e., a larger heat exchange area between the anode support layer 2D and the cathode flow path 8, compared to the configuration of the above embodiment. The larger heat exchange area reduces the temperature on the anode side further, thereby further suppressing steam oxidation in a high-temperature environment, and as a result, the corrosion resistance of the interconnector 4 can be ensured.
[0042] The effects of this embodiment and its modified examples are summarized as follows.
[0043] In this embodiment, a solid oxide fuel cell is provided in which a plurality of power generating cells 2 each having a solid electrolyte plate, an anode electrode disposed on one surface of the solid electrolyte plate, an anode support layer 2D supporting the anode electrode, a cathode electrode disposed on the other surface of the solid electrolyte plate, and a cathode support layer 2B supporting the cathode electrode are stacked in the thickness direction via an interconnector 4 that electrically connects the anode support layer 2D of one adjacent power generating cell 2 to the cathode support layer 2B of the other adjacent power generating cell 2. The anode support layer 2D and the cathode support layer 2B are made of ferritic stainless steel, and the interconnector 4 is made of ferritic stainless steel containing aluminum. As a result, an alumina layer is formed on the outermost layer of the interconnector 4 during operation of the fuel cell or during the stacking process. The formation of the alumina layer suppresses steam oxidation of the interconnector 4, thereby ensuring corrosion resistance.
[0044] In this embodiment, the thickness of the base material of the interconnector 4 is thinner than the thickness of the support layers 2B, 2D. This makes it possible to properly maintain a balance between the compressive load input from the interconnector 4 to the power generation cell 2 in the stacking process and the strength of the support layers 2B, 2D. Furthermore, by making the base material of the interconnector 4 thinner, the heat capacity of the interconnector 4 is reduced, thereby making it possible to shorten the time required to start up the fuel cell.
[0045] In this embodiment, the interconnector 4 is formed of a single plate material and includes a cathode side rib 10 protruding toward the cathode electrode and an anode side rib 11 protruding toward the anode electrode, with the cathode side rib 10 contacting the cathode support layer 2B and the anode side rib 11 contacting the anode support layer 2D. This brings the anode support layer 2D, which supports the anode electrode as a heat generating part, into contact with the cathode flow path 8 through which the cathode gas flows at a higher flow rate than the anode gas, so that the temperature of the heat generating part can be further reduced. Furthermore, by reducing the temperature of the heat generating part, steam oxidation in a high-temperature environment is suppressed, so that the corrosion resistance of the interconnector 4 can be ensured.
[0046] According to the modified example of the present embodiment, the width of the contact portion between the anode side rib 11 and the anode support layer 2D is wider than the width of the contact portion between the cathode side rib 10 and the cathode support layer 2B. This increases the heat exchange area between the anode support layer 2D and the cathode flow channel 8, thereby improving the cooling effect of the heat generating portion.
[0047] In this embodiment, the connection portion of the interconnector 4 with the anode support layer 2D of one adjacent power generating cell 2 and the connection portion with the cathode support layer 2B of the other adjacent power generating cell 2 are joined via an insert member 13. The insert member 13 is mainly composed of a material having a smaller mutual diffusion coefficient with aluminum at the joining surface compared to a case in which the interconnector 4 is joined to the anode support layer 2D and the cathode support layer 2B without the insert member 13. This suppresses the outflow of aluminum from the interconnector 4 to the insert member 13, and therefore the alumina layer is formed stably.
[0048] In this embodiment, the main component of the insert member 13 is, for example, nickel. Nickel has a significantly smaller mutual diffusion coefficient with aluminum than FSS, and is therefore highly effective in suppressing the outflow of aluminum from the interconnector 4.
[0049] In this embodiment, the insert member 13 may be a material containing aluminum. By containing aluminum in the insert member 13, the aluminum concentration gradient between the interconnector 4 and the insert member 13 becomes small, so that outflow of aluminum from the interconnector 4 can be suppressed.
[0050] In this embodiment, the insert member 13 may be a paste containing ferritic stainless steel as a main component and aluminum. The paste-like insert member 13 makes it easier to adjust the aluminum content compared to a foil-like insert member, and the heating temperature in the lamination process can be reduced.
[0051] In this embodiment, before the lamination process, a pre-oxidation process may be performed in which an oxidation treatment is performed on the interconnector 4. By forming the alumina layer of the outermost surface of the interconnector 4 in advance, the period during which the alumina layer is formed during operation of the fuel cell is shortened, thereby improving the steam oxidation resistance in low temperature ranges such as at start-up.
[0052] In this embodiment, when the pre-oxidation step is performed, the oxidation treatment is performed at 900° C. or higher. This causes the alumina layer to be formed to be so-called α-alumina, which is highly stable and unlikely to grow abnormally, and therefore the supply rate of aluminum for forming the alumina layer during the operation of the fuel cell is suppressed, making it possible to maintain the steam oxidation resistance for a long period of time.
[0053] Although the embodiments of the present invention have been described above, the above-mentioned embodiments merely show some of the application examples of the present invention, and it is not intended that the technical scope of the present invention be limited to the specific configurations of the above-mentioned embodiments.
Claims
1. A solid oxide fuel cell comprising a plurality of power generating cells, each having a solid electrolyte plate, an anode electrode disposed on one surface of the solid electrolyte plate, an anode support layer supporting the anode electrode, a cathode electrode disposed on the other surface of the solid electrolyte plate, and a cathode support layer supporting the cathode electrode, stacked in a thickness direction via an interconnector that electrically connects the anode support layer of one of the power generating cells to the cathode support layer of the other of the power generating cells, the anode support layer and the cathode support layer are made of ferritic stainless steel; The interconnector is made of ferritic stainless steel containing 2 wt % or more of aluminum.
2. 2. The solid oxide fuel cell according to claim 1, A solid oxide fuel cell, wherein the thickness of the substrate of the interconnector is thinner than the thicknesses of the anode support layer and the cathode support layer.
3. 3. The solid oxide fuel cell according to claim 1, the interconnector is formed of a single plate material and includes a cathode side rib protruding toward the cathode electrode and an anode side rib protruding toward the anode electrode, a cathode side rib in contact with the cathode support layer and an anode side rib in contact with the anode support layer,
4. The solid oxide fuel cell according to claim 3, a width of a contact portion between the anode side rib and the anode support layer is wider than a width of a contact portion between the cathode side rib and the cathode support layer.
5. The solid oxide fuel cell according to any one of claims 1 to 4, a connection portion of the interconnector with the anode support layer of one of the adjacent power-generating cells and a connection portion of the interconnector with the cathode support layer of the other of the adjacent power-generating cells are joined via an insert member, A solid oxide fuel cell, wherein the insert member is primarily composed of a material that has a smaller mutual diffusion coefficient with aluminum at the joining surface compared to when the interconnector is joined to the anode support layer and the cathode support layer without the insert member.
6. The solid oxide fuel cell according to claim 5, A solid oxide fuel cell, wherein the insert member is mainly composed of nickel.
7. 7. The solid oxide fuel cell according to claim 5, The insert member is a solid oxide fuel cell containing aluminum.
8. The solid oxide fuel cell according to claim 5, A solid oxide fuel cell, wherein the insert member is a paste containing ferritic stainless steel as a main component and aluminum.
9. A method for producing a solid oxide fuel cell includes a lamination step of laminating a plurality of power generating cells in a thickness direction via an interconnector that electrically connects the anode support layer of one of the power generating cells and the cathode support layer of the other of the power generating cells, the power generating cells having a solid electrolyte plate, an anode electrode disposed on one surface of the solid electrolyte plate, an anode support layer supporting the anode electrode, a cathode electrode disposed on the other surface of the solid electrolyte plate, and a cathode support layer supporting the cathode electrode, the lamination step comprising: The anode support layer and the cathode support layer are made of ferritic stainless steel, The interconnector is made of ferritic stainless steel containing 2 wt % or more of aluminum, A method for producing a solid oxide fuel cell, comprising the steps of: performing a pre-oxidation step of subjecting the interconnector to an oxidation treatment before performing the lamination step.
10. 10. The method for producing a solid oxide fuel cell according to claim 9, The method for producing a solid oxide fuel cell, wherein the oxidation treatment in the pre-oxidation step is carried out at 900° C. or higher.
Citation Information
Patent Citations
Unit battery cell for fuel battery
JP2006236989A
fuel cells
JP2015514281A
Fuel cell
JP2019185883A
Solid-oxide fuel cell
WO2016199223A1